Unreliable organic marketing in the context of organic production conditions - Hasińska, Izabela (Przegląd Prawa Rolnego, 2023)
The aim of the study was to answer the question whether the new legal regulations intended to protect consumers against unreliable organic marketing (“greenwashing”) are sufficient. In this regard, the conditions of organic production, the principles of certification, the labelling of organic products, the marketing practices and the sanctions for the violation of organic farming responsibilities have been analysed. It has been determined, among other things, that the clarification in the new legislative acts of the procedures needed to be completed in order to take up organic production, as well as the operation of the control and certification system, will certainly ensure to a much higher degree the desired quality of an organic product. This objective will also be achieved owing to the harmonisation of the labelling of organic products and the now mandatory requirement to provide information on the product origin. Furthermore, the sanctions for non-compliance with organic farming regulations, now elaborated and clarified in more detail in the legal provisions adopted, may also be seen as strengthening consumer protection against unreliable organic marketing. The sanction that seems of particular value is the conditioning of the amount of the fine on the extent of the financial benefit that the operator concerned has obtained or could obtain for products marketed contrary to the organic production conditions is another factor.